2023
DOI: 10.3390/children10010141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Depressive Symptoms among Young Adolescents in Malaysia: A Cross-Sectional Study

Abstract: Depression is the most common mental health problem affecting adolescents globally, wherein its increasing prevalence together with the negative health impacts escalates the need for further research in this area. This work determined the prevalence and factors associated with depressive symptoms among young adolescents in Malaysia. A total of 1350 adolescent aged 13 to 14 years in school across nine secondary schools in Selangor state, Malaysia participated in a cross-sectional study. Independent variables we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…Similar to the finding of this study, another study from Nepal revealed that female adolescents were almost twice more at odds of being depressed than their male counterparts [35]. Similar phenomenon has also been observed in other nations such as Malaysia and Central Uganda, where female were found to have almost two-to-three-folds increase in odds of depression than males [41,42]. Female adolescents experience hormonal changes and stressful events during puberty much more than males, which might make them more prone to anxiety and stress [34].…”
Section: Plos Global Public Healthsupporting
confidence: 90%
“…Similar to the finding of this study, another study from Nepal revealed that female adolescents were almost twice more at odds of being depressed than their male counterparts [35]. Similar phenomenon has also been observed in other nations such as Malaysia and Central Uganda, where female were found to have almost two-to-three-folds increase in odds of depression than males [41,42]. Female adolescents experience hormonal changes and stressful events during puberty much more than males, which might make them more prone to anxiety and stress [34].…”
Section: Plos Global Public Healthsupporting
confidence: 90%
“…Unsurprisingly, since life satisfaction is a positive construct, the negative emotions and psychological states, such as hopelessness or depressed mood, are often negatively correlated with it [12,13]. Depression is a common mental health problem in adolescence, with a surplus among girls [14], and even subclinical depressive symptoms may have a great impact on well-being [15].…”
Section: Introductionmentioning
confidence: 99%